Adab Murid Terhadap Guru Dalam Perspektif Hadits - Abnisa, Almaydza Pratama (STAI Asy-Syukriyyah, 2022)
Seeking knowledge requires understanding and ethics based on religious arguments so that Allah SWT. facilitates the pursuit of knowledge. It is important for Muslims to study the arguments related to the obligation to study and understand the ethics of a student in studying so that they can obtain knowledge to the fullest. A student in gaining knowledge should pay attention to several things that need to be prepared. One of them is having good intentions. Sincere intentions in his heart. The intention is solely to learn because of Allah ta'ala. In addition, a student must also have good manners in his pursuit of knowledge. The most important figure as a role model for students to have commendable morals is the Prophet Muhammad. Rasulullah saw is a noble creature. His main task was sent to the world is to perfect morals. He taught and exemplified commendable behavior to his friends. Then the friends transmit what they get to others, so that these teachings reach us today. These teachings have come down to us in the form of hadiths.